Calculate the Fourier transform of $f_{ZOH}$ (the zero-order hold reconstruction of a sampled signal).

Where $f_{ZOH} (t)= f(kT), \ \ kT \leq t < (k+1)T,$ and the sampled signal is

$$f_s = f(t) \sum^\infty_{-\infty} \delta (t - kT).$$


First writing the $f_{ZOH} (t)$ as a convolution between impulse response and sampled signal:

$$f_{ZOH} (t) = \left( \sum^{\infty}_{k=-\infty} f(kT) \delta(t-kT) \right) * h(t) = \sum^{\infty}_{k=-\infty} f(kT)h(t-kT).$$

But the shape function for the impulse response is the rectangular pulse function:

$$f_{ZOH} (t) = \sum^{\infty}_{k=-\infty} f(kT) \Pi (t-kT).$$

Now we want to calculate the Fourier transform of $f_{ZOH}$:

$$FT \Big[ f_{ZOH} \Big] = \frac{1}{T} F(\nu ) \sum^{\infty}_{k=-\infty} \Pi \left( \nu - \frac{k}{T} \right) = \frac{1}{T} \sum^{\infty}_{k=-\infty} F\left(\frac{k}{T}\right) FT \left[ \Pi \left(\nu - \frac{k}{T}\right) \right]$$

$$= \frac{1}{T} \sum^{\infty}_{k=-\infty} F\left(\frac{k}{T}\right) \textrm{sinc} \left(\nu - \frac{k}{T}\right).$$

But I was told that this is not the correct answer. What is wrong here?

Any explanation would be greatly appreciated.


The Fourier transform of the sampled signal $$f_s = f(t) \sum^\infty_{-\infty} \delta (t - kT)$$ is $$\begin{align} F_s(\nu)&=F(\nu)*\mathcal F\left\{\sum^\infty_{k=-\infty} \delta (t - kT)\right\}\\ &=F(\nu)*\sum^\infty_{k=-\infty} \frac{1}{T}\delta \left(\nu - \frac{k}{T}\right)\\ &=\frac{1}{T}\sum^\infty_{k=-\infty} F\left(\nu - \frac{k}{T}\right) \end{align} $$ so the Fourier transform $F_{\mathrm{ZOH}}(\nu)$ of $f_{\mathrm{ZOH}}(t)=f_s(t)*h_{\mathrm{ZOH}}(t)$ is $$ F_{\mathrm{ZOH}}(\nu)=\mathcal F\left\{(f_s*h_{\mathrm{ZOH}})(t)\right\}=F_s(\nu)H_{\mathrm{ZOH}}(\nu)=H_{\mathrm{ZOH}}(\nu)\frac{1}{T}\sum^\infty_{k=-\infty} F\left(\nu - \frac{k}{T}\right) $$ The Fourier transform $\mathcal F\left\{f_{\mathrm{ZOH}}(t)\right\}$ can be also evaluated as $$ \begin{align} F_{\mathrm{ZOH}}(\nu)&=F(\nu)*\mathcal F\left\{\sum^\infty_{k=-\infty} h_{\mathrm{ZOH}}(t - kT)\right\}\\ &=F(\nu)*\sum^\infty_{k=-\infty} \frac{1}{T} H_{\mathrm{ZOH}}\left(\frac{k}{T}\right)\delta\left(\nu - \frac{k}{T}\right)\\ &=\sum^\infty_{k=-\infty} \frac{1}{T} H_{\mathrm{ZOH}}\left(\frac{k}{T}\right)F\left(\nu - \frac{k}{T}\right) \end{align} $$ so we have $$ F_{\mathrm{ZOH}}(\nu)=H_{\mathrm{ZOH}}(\nu)\frac{1}{T}\sum^\infty_{k=-\infty} F\left(\nu - \frac{k}{T}\right)=\sum^\infty_{k=-\infty} \frac{1}{T} H_{\mathrm{ZOH}}\left(\frac{k}{T}\right)F\left(\nu - \frac{k}{T}\right) $$ For the ZOH we use $$h_{\mathrm{ZOH}}(t)=\begin{cases}1 & 0\le t\le T\\ 0 & \text{otherwise}\end{cases}$$ with Fourier tansform $$ H_{\mathrm{ZOH}}(\nu)=\frac{\sin(\pi\nu T)}{\pi\nu}\mathrm{e}^{-\mathrm j \pi\nu T}=T\mathrm{sinc(\pi\nu T)}\mathrm{e}^{-\mathrm j \pi\nu T} $$ and then $$ F_{\mathrm{ZOH}}(\nu)=\mathrm{sinc(\pi\nu T)}\mathrm{e}^{-\mathrm j \pi\nu T}\sum^\infty_{k=-\infty} F\left(\nu - \frac{k}{T}\right) $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.